Mesomechanical damage of fiber mortar under temperature difference. Issue 2 (25th January 2023) - Zhang, Yan; Li, Zhihao; Li, Ning; Li, Sheng; Liu, Jiahao; Ye, Wanjun; Zheng, Xuanrong
Abstract: The present study aims to establish a mesomechanical damage model for the description of anisotropic damage by mesocracking under temperature difference condition. With the basic solution of Eshelby theory and the Clapeyron equation, a mechanics framework is developed for cement materials, which are considered to be heterogeneous materials consisting of a cement stone matrix and imbedded penny-shaped microcracks. From the mesomechanical analysis, the critical conditions corresponding to the failure of fiber mortar under different initial crack density conditions are obtained. Furthermore, the Clapeyron equation is used to describe the relationship between the stress and the initiation or expansion of the fiber mortar crack and the damage evolution rule is expressed by the energy equation of the stiffness coefficient. The proposed model can accurately quantify the factors such as fiber distribution, microcrack density, temperature differences and the relationship between directional microcracks and crack strength in mortar. The results verified by laboratory tests and numerical simulations show that as the temperature difference increases from 0 °C to 75 °C, the cracking strength of the fiber mortar decreases and the number of cracks increases in the form of a power exponential function, which proves the micromechanical damage the validity of the model.